Carbohydrate response element binding protein directly promotes lipogenic enzyme gene transcription - Ishii, Seiji (National Academy of Sciences, 2004)
Carbohydrate response element (ChRE)-binding protein (ChREBP) is a recently discovered transcription factor that is activated in response to high glucose concentrations in liver independently of insulin. ChREBP was first identified by its ability to bind the ChRE of the liver pyruvate kinase (LPK) gene. We recently reported that the increase in expression of multiple liver lipogenic enzyme mRNAs elicited by feeding a high-carbohydrate diet as well as that of LPK mRNA is markedly reduced in mice lacking ChREBP gene expression (ChREBP(-/-)) in comparison to WT mice. The present study provides evidence for a direct and dominant role of ChREBP in the glucose regulation of two key liver lipogenic enzymes, acetyl-CoA carboxylase (ACC) and fatty acid synthase (FAS). ACC, FAS, and LPK mRNA levels were higher in WT hepatocytes cultured with high (25 mM) rather than low (5.5 mM) glucose medium, but there was no effect of glucose concentration on these mRNA levels in ChREBP(-/-) hepatocytes. Similarly, reporter constructs containing ACC, FAS, or LPK gene ChREs were responsive to glucose when transfected into WT but not ChREBP(-/-) hepatocytes, and glucose transactivation of the constructs in ChREBP(-/-) hepatocytes was restored by cotransfection with a ChREBP expression plasmid. ChREBP binding to ACC, FAS, and LPK ChRE sequences in vitro was demonstrated by electrophoretic mobility super shift assays. In vivo binding of ChREBP to ACC, FAS, and LPK gene promoters in intact liver nuclei from rats fed a high-carbohydrate diet was demonstrated by using a formaldehyde crosslinking and chromatin immunoprecipitation procedure.